Avaliação da presença de macroprolactinemia em amostras hiperprolactinêmicas, através da concentração de prolactina monomérica dosada após precipitação com polietileno glicol - Maria do Carmo Dias Gontijo (2016)
Macroprolactin interference is a common problem in the interpretation of immunoassays for prolactin. Identifying macroprolactinemia can prevent errors in diagnosis and subsequent delivery of treatment to patients. The search for macroprolactin after polyethylene glycol (PEG) precipitation is the most commonly used method in clinical laboratories. This study aimed to evaluate the implementation of macroprolactin assessment in hyperprolactinemic samples, with the interpretation of the results based on comparisons between the concentration of post-PEG monomeric prolactin with an appropriate reference range from the Serviço de Medicina Laboratorial (SML) of the Hospital das Clinicas, Universidade Federal de Minas Gerais (HC/UFMG). Study objectives included validation of the commercial reagent for prolactin measurement in the analytical system Architect® (Abbott); checking of reference intervals for post-PEG monomeric prolactin; comparison of the two criteria of interpretation for post-PEG macroprolactin assessment, comparing the results to some samples processed by Gel filtration chromatography (GFC); and to assess the prevalence of macroprolactinemia in the study population. Validation of the commercial reagent for the prolactin assay was performed using tests of precision, linearity and accuracy. To check the post-PEG monomeric prolactin reference ranges, we used samples from 40 healthy people. The macroprolactin assessment by PEG precipitation was performed on 112 hyperprolactinemic samples, 96 women (18-80 years old, mean 38) and 16 men (21-65, 45). We compared both interpretations of the results from the macroprolactin test. A subset of 25 samples was sent to the GFC and compared with results from the PEG precipitation assessment. The validations of the commercial reagent for prolactin and of the reference range for prolactin post PEG were in agreement with the predetermined specifications of quality. Comparison of the post-PEG monomeric prolactin concentration with an appropriate reference range showed greater specificity than the conventional criterion percentage of postPEG prolactin recovery by identifying samples with both excess macroprolactin and monomeric bioactive prolactin and reducing the rate of indeterminate outcomes. Furthermore, most of the results of samples sent to the GFC were in concordance with the results found in this study. The prevalence of macroprolactinemia found was 19%. Based on these results, we recommend the implementation of the macroprolactin assessment with PEG precipitation test at the SML of HC/UFMG, for all hyperprolactinemic samples. Further, the interpretation of the test by comparing post-PEG monomeric prolactin concentration with a suitable reference range should be adopted as it outperformed existing criteria.